Olahraga dan Depresi pada Wanita Hamil - Nabila Ayuningtyas (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Pregnancy is a time of social, psychological, behavioral and biological change thus, it has been identified as a factor that contributes to the decline in sports behavior among women. Inactivity during pregnancy has a devastating effect on both women and the fetus, in the prenatal phase women who do not exercise neglect many health benefits. Health behavior carried out by pregnant women in the form of exercise. Sports activities are a form of behavior carried out by pregnant women in maintaining and improving the health of their pregnancies as well as preventive measures for labor diseases or complications. For example, exercise during pregnancy is associated with a reduced risk of preeclampsia, depression and gestational diabetes. Research conducted concluded that exercise has the effect of reducing depression in pregnant women. Adequate exercise is very important for pregnant women, because it has proven beneficial for the health of the mother and fetus. Therefore, the implementation of interventions aimed at increasing the level of physical activity is highly recommended. physical activity interventions, useful for weight loss during pregnancy, and reduction in pregnancy-related symptoms, such as depression and pregnancyrelated pain. Exercise has the potential to help overcome obstacles to increasing the level of physical activity among pregnant women.